Turning words into numbers: Measuring news media coverage of shortages - Lin Chen; Stephanie Houle (Bank of Canada, 2023)
We generate high-frequency and up-to-date indicators to monitor news media coverage of supply (raw, intermediate and final goods) and labour shortages in Canada. We use natural language processing to construct two news-based indicators and time-varying topic narratives to track Canadian media coverage of these shortages from 2000 to 2022. This makes our indicators an insightful alternative monitoring tool for policy. Notably, our indicators track well with monthly price indexes and measures from the Bank of Canada's Business Outlook Survey, and they are highly correlated with commonly tracked indicators of supply constraint. Moreover, the news-based indicators reflect the attention of the public on pressing issues.
Keywords: C55; C82; E37; 330; Coronavirus disease (COVID-19); Econometrics and statistical methods; Monetary policy and uncertainty; Recent economic and financial developments